Case Report: Guillain-Barré Syndrome as Primary Presentation of Systemic Lupus Erythematosus (SLE-GBS) in a Teenage Girl - Beshir, Elham; Belt, Ernestina; Chencheri, Nidheesh; Saqib, Aqdas; Pallavidino, Marco; Terheggen, Ulrich; Abdalla, Abdalla; Herlitz, Leal; Sharif, Elsadeg; Bitzan, Martin (Frontiers in Pediatrics, 2022)
Peripheral nervous system involvement accounts for fewer than 10% of SLE cases with neuropsychiatric manifestations. Guillain Barré Syndrome (GBS) as the presenting, major manifestation of pediatric SLE is extremely rare, and the best treatment approach is unknown. A 14-year-old, previously healthy female teenager presented with classic features of GBS with ascending, progressive bilateral muscle weakness leading to respiratory insufficiency within five weeks of symptom onset, associated with typical protein-cell dissociation in cerebro-spinal fluid and nerve root enhancement demonstrated by spinal MRI. Subsequently, elevated anti-dsDNA and anti-Smith/RNP and anti-SS-A and -B antibody concentrations were detected in serum, suggestive of SLE. Despite treatment with intravenous immunoglobulin (IVIg) and methylprednisolone pulses, the patient required endotracheal intubation and ventilation, followed by a second course of IVIg, rituximab, and eventually plasma exchange (PLEX) therapy. The diagnosis of lupus-associated GBS was corroborated by a kidney biopsy demonstrating lupus nephritis WHO class II with “full house” immunofluorescence pattern. After 14 PLEX sessions, her muscle strength and respiratory efforts had improved substantially. Treatment was completed with two more rituximab infusions, followed by a limited, 2-month-period of mycophenolate mofetil, in addition to hydroxychloroquine and tapering doses of oral prednisolone. Five weeks after the last PLEX treatment, she had regained her usual strength and achieved full, sustained recovery from GBS. C3, C4 and urinalysis quickly normalized while moderate anti-dsDNA and high-level anti-Smith and Sjogren antibodies persist 15 months after disease onset, with no other manifestations of lupus or lupus nephritis. A review of the literature revealed that cconventional GBS therapy may not be adequate to treat SLE GBS. SLE should be included in the differential diagnosis of GBS. Importantly, treatment experiences and outcomes of such cases need be reported to inform future treatment recommendations.